Bilateral fusion of permanent maxillary incisors - Manoj Kumar Hans; Shashit Shetty; Hitesh Chopra (Wolters Kluwer Medknow Publications, 2011)
Dental fusion is a rare developmental anomaly, which is included in the anomalies of tooth morphology or shape. Fusion can occur at the level of enamel or enamel and dentin, which results in the formation of a single tooth with enlarged clinical crown. Fusion is more common in deciduous dentition. Incisors are reported to be fused in primary and permanent dentition, but bilateral fusion is a rare occurrence. The prevalence of bilateral fusion in the permanent dentition is less frequent than unilateral fusion and is reported to be around 0.05%. The authors report a case of a 20-year-old male with bilateral fusion of maxillary central and lateral incisors. Multi-disciplinary treatment approach is essential to get the desired esthetic result. The best way to manage these difficult cases depends on a number of factors including the knowledge and technical skills of the practitioner.